The South Kalimantan Ulama’s Leadership in Covid-19 Pandemic Era - M. Kholis Amrullah (INNOVATIO: Journal for Religious Innovation Studies, 2020)
Abstract: Ulama are community leaders who have the highest religious competence in society and deliver scholars to become religious leaders. Apart from religious leadership, ulama also have social leadership that is able to control many individuals or groups. This study aims to reveal the form of ulama leadership in South Kalimantan during the Covid-19 conditions. This study uses a qualitative approach with descriptive analysis. The data is taken from some information posted on trusted websites. The results showed that ulama in South Kalimantan practiced transformational religious leadership in society. Ulama in the context of this research are ulama in South Kalimantan who often get the spotlight from the public. With the interaction of scholars on leadership, the leadership is modeled on religious leadership. Religious leadership offers religious, theological, moral, ethical, and spiritual guidance on most aspects of the daily life of Muslims. Keywords: leadership, ulama, the covid-19 pandemic. Abstrak: Ulama merupakan tokoh masyarakat yang memiliki kompetensi beragama tertinggi di dalam masyarakat dan menghantarkan ulama menjadi pemimpin agama. Selain kepemimpinan beragama, ulama juga memiliki kepemimpinan sosial yang mampu mengendalikan banyak individu atau kelompok. Penelitian ini bertujuan untuk mengungkap bentuk kepemimpinan ulama di Kalimantan Selatan selama kondisi covid-19. Penelitian ini menggunakan pendekatan kualitatif dengan analisis deskriptif. Data penelitian diambil dari beberapa informasi yang dimuat di situs web terpercaya. Hasil penelitian menunjukkan bahwa ulama di Kalimantan Selatan mempraktikkan kepemimpinan transformational beragama dalam masyarakat. Ulama dalam konteks penelitian ini adalah ulama di Kalimantan Selatan yang sering mendapat sorotan dari public. Dengan adanya keterlibatan ulama pada kepemimpinan, maka kepemimpinannya bermodel kepemimpinan religius. Kepemimpinan religius menawarkan bimbingan religius, teologis, moral, etis, dan spiritual pada sebagian besar aspek kehidupan sehari-hari umat Islam. Kata-kata kunci: kepemimpinan, ulama, pandemi covid-19.